Report of the Working Group on Border Area Development Programme - Planning Commission (Planning Commission, Government of India, 2001)
The Border Area Development Programme (BADP), initiated during the Seventh Five-Year Plan and subsequently reoriented in the Eighth and Ninth Plans, aims to promote balanced development and strengthen security in India’s international border areas. Initially focusing on infrastructure such as roads, power, drinking water, health, and educational facilities, the programme has progressively evolved into a State-level initiative covering seventeen border States, including those adjoining Bangladesh, Myanmar, China, Bhutan, and Nepal. BADP is fully centrally funded and provides Special Central Assistance to States, with allocations determined by border length, population, and area of border blocks. The programme emphasizes addressing the specific socio-economic and infrastructural needs of remote and inaccessible border areas while promoting national integration and community engagement. Eligible schemes include education, vocational training, employment generation, social infrastructure, and critical connectivity projects, with limited allocation for security-related initiatives. Execution of schemes is flexible, allowing State Governments, central agencies, para-military forces, voluntary organizations, and local governance institutions to participate, ensuring local ownership and participation. Policy oversight is provided by an Empowered Committee at the Planning Commission, while Screening Committees at the State level approve and monitor individual schemes. Funds are released in two instalments based on approved schemes and quarterly progress reports, ensuring accountability and transparency. The Working Group for BADP for the Tenth Plan was constituted to assess achievements and shortcomings of the Ninth Plan, recommend policy frameworks, and develop strategies for integrated, long-term development of border areas, with active involvement of the local population and grassroots institutions, thereby enhancing governance, infrastructure, and socio-economic resilience in India’s sensitive border regions.
Government of India Planning Commission December 2001
Keywords: Border Area Development Programme; BADP; Tenth Five-Year Plan; Infrastructure Development; Remote Areas; Central Assistance; State Governments; Screening Committee; Empowered Committee; International Borders; Security; Community Participation